Time interval between E and E′ waves can predict complicated clinical course in patients with acute pulmonary embolism. Issue 6 (3rd March 2021) - Acar, Emrah; Kilicgedik, Alev; Izci, Servet; Inanir, Mehmet; Yilmaz, Mehmet Fatih; Gokce, Mustafa; Izgi, Ibrahim Akin; Kirma, Cevat
Abstract: Purpose: Acute pulmonary embolism is a life‐threatening cardiothoracic emergency leading to right ventricle systolic and diastolic dysfunction. In the present study, we investigated the right ventricle diastolic function and its predictive value in patients with acute pulmonary embolism. Material and methods: Were prospectively recruited in this study 621 patients diagnosed with acute pulmonary embolism between December 2015 and June 2019. Among them, 173 were excluded, leaving 448 patients for follow‐up. Transthoracic echocardiography was performed for the evaluation of the right ventricle systolic and diastolic indices. At 30‐day follow‐up, the patients were allocated either into the benign or in the complicated clinical course group. Results: The group with complicated clinical course had higher value of pulmonary artery systolic pressure (PASP), right/left ventricle diameter ratio, E‐wave velocity, E/A ratio, A′ wave velocity, E/E′ ratio, and time interval between E and E′ waves ( P  < .05), but lower values of tricuspid annular plane systolic excursion, A‐wave velocity, isovolumetric relaxation time, deceleration time, E′, and E′/A′ ( P  < .05). Complicated clinical course was associated with shorter isovolumetric relaxation time ( r  = .564, P  < .001), E/E′ ( r  = .495, P  < .001), and TE‐E′ ( r  = .596, P  < .001). Receiver operator characteristic curve analysis showed that TE‐E′ had the largest area under curve (TE‐E′ 0.82, IVRT 0.77, E/E′ 0.72). A cut‐off value of TE‐E′ = 70 milliseconds had an 81.1% sensitivity and 71.4% specificity for the prediction of the complicated clinical course. Conclusion: The assessment of the right ventricle diastolic function could predict the complicated clinical course in patients with acute pulmonary embolism.